Pancreatogenic type 3C diabetes - Anca Pantea-Stoian; Georgiana Ditu; Mircea Diculescu; Mircea Manuc; Andra Iulia Suceveanu; Dana Manuc; Camelia Diaconu; Adrian Paul Suceveanu; Cornelia Nitipir; Razvan Hainarosie; Catalina Poiana; Cristian Serafinceanu (Journal of Mind and Medical Sciences)
Background. The relationship between chronic pancreatitis and diabetes is well established. This form of diabetes is secondary to exocrine pancreatic disorder and is known as diabetes mellitus type 3c (T3cDM). Materials and Methods. In this retrospective study we included 261 patients, 59 patients being diagnosed with chronic pancreatitis and secondary diabetes mellitus, and admitted in the Fundeni Clinical Institute, 2nd Department of Gastroenterology or N.C. Paulescu Institute/ Carol Davila University of Medicine and Pharmacy. Results and Discussions. Patients were 22.2% women and 77.8% men, with an average age of 56.8 years and 53.4 years respectively. 63% came from urban areas. The mean duration of chronic pancreatitis was six years. Non-diabetic patients were compared with patients who were previously diagnosed with T3cDM and who had been analyzed for body mass index (BMI). Imaging investigations were also performed to confirm pseudotumors or pancreatic tumours. Patients already considered non-diabetic had basal blood glucose values and were mostly overweight and obese. In this context, insulin resistance cannot be excluded for this group of patients. Conclusions. T3cDM is a new pathological entity that needs to be explored more deeply, and that should benefit from both a diagnostic stratification and treatment.